Comparison between numerical simulation and on-orbit experiment of oscillating heat pipes. (June 2017) - Daimaru, Takurou; Nagai, Hiroki; Ando, Makiko; Tanaka, Kosuke; Okamoto, Atsushi; Sugita, Hiroyuki
Highlights: We developed a numerical model for reproducing the phenomena inside OHP. The model was validated using on-orbit experimental data from JAXA. The OHP can start when liquid slugs exist in the heating section. Initial vapor-liquid distributions do not affect steady state performance. The OHP has startup difficulty when liquid slugs localize in the cooling section. Abstract: This study investigated the startup behavior of Oscillating Heat Pipes (OHPs) by comparing numerical simulation and on-orbit experimental data. Previous studies suggested that initial vapor-liquid distribution affects startup behavior. However, they provided no experimental evidence to validate this hypothesis because experimentally reproducing and specifying initial vapor-liquid distribution in OHPs is virtually impossible. Thus, a numerical approach is necessary to generate the initial vapor-liquid distribution and to understand the internal thermofluid behavior of OHPs. In this study, a one-dimensional numerical model of an OHP with check valves was first developed. Then, the model was compared with data from an on-orbit experiment. Finally, simulation of OHP startup behavior with several types of initial vapor-liquid distributions showed that OHP startup difficulty is due to localization of liquids in the cooling section.